(untitled) (International Journal of Agriculture and Sustainable Development, 2024)
While individuals may possess a solid comprehension of agricultural operations, the agriculture business is progressively emphasizing data and necessitates more precise and sophisticated data and technology than in previous times. The agriculture industry is being improved by many sophisticated communication technologies, such as the Internet of Things (IoT). The quick progress of these cutting-edge technologies has significantly revolutionized almost every industry, including advanced agriculture, which has shifted from a qualitative to a quantitative approach. This significant transformation has disturbed conventional agricultural practices and presented new obstacles in a sequence of persistent difficulties. This extensive study piece highlights the capacity of the Internet of Things (IoT) to enhance agriculture and the difficulties that arise when integrating these cutting-edge technologies with current agricultural systems. This paper provides a concise overview of the most recent sensor-based technologies employed in advanced agricultural applications. Efficient management techniques are crucial for a variety of sensors used in certain agricultural activities, including soil preparation, irrigation systems, and pest and disease control. This examination covers all pertinent processes within the agricultural system, such as planting, harvesting, packaging, shipping, and new technologies, that farmers can utilize. This review study highlights the use of unmanned aerial vehicles (UAVs) and other tools for agricultural monitoring and other beneficial activities, such as maximizing crop yields. Furthermore, intricate Internet of Things (IoT) applications are also encompassed. After doing extensive research, we have discovered encouraging prospects for the implementation of Internet of Things (IoT) technology in the field of sustainable agriculture.